Sugarcane bagasse pulping and bleaching: Thermal and chemical characterization - Pereira, Paulo H. Fernandes [UNESP]; Voorwald, Herman Cornelis Jacobus [UNESP]; Cioffi, Maria Odila H. [UNESP]; Mulinari, Daniella Regina; da Luz, Sandra M.; da Silva, Maria Lucia Caetano Pinto (My University, 2011)
Cellulose fibers were isolated from sugarcane bagasse in three stages. Initially sugarcane bagasse was subjected to a pre-treatment process with hydrolyzed acid to eliminate hemicellulose. Whole cellulosic fibers thus obtained were then subjected to a two-stage delignification process and finally to a bleaching process. The chemical structure of the resulting cellulose fibers was studied by Fourier Transform Infrared (FTIR) spectroscopy. Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD) were used to analyze the effects of hydrolysis, delignification, and bleaching on the structure of the fibers. Two different thermal analysis techniques were used to study the bleaching cellulose fibers. These techniques confirmed that cellulose fibers were isolated from sugarcane bagasse. A future goal is to use these fibers as reinforcement elements in composites, organic-inorganic hybrid, and membranes for nanofiltration.
Keywords: Bleaching and morphology; Cellulose; Sugarcane bagasse